Chasing protons in lithium-ion batteries. Issue 73 (30th August 2022) - Chen, Zonghai
Abstract : The parasitic reaction between the cathode and the electrolyte is facilitated by the coordination bonding between the carboxyl groups and the interfacial transition metal ions. A stable cathode electrolyte interface can be achieved by (1) blocking coordination bond, (2) retarding electron transfer, and (3) hindering the diffusion of protons towards the cathode material. Abstract : Parasitic reactions between delithiated cathode materials and non-aqueous electrolytes have been a major barrier that limits the upper cutoff potential of cathode materials. It is of great importance to suppress such parasitic reactions to unleash the high-energy-density potential of high voltage cathode materials. Although major effort has been made to identify the chemical composition of the cathode electrolyte interface using various cutting edge characterization tools, the chemical nature of parasitic reactions remains a puzzle. This severely hinders the rational development of stable high voltage cathode/electrolyte pairs for high-energy density lithium-ion batteries. This feature article highlights our latest effort in understanding the chemical/electrochemical role of the cathode electrolyte interface using protons as a chemical tracer for parasitic reactions.